Numerical Study on the Flow Mechanism of Compressor Rotor Blade Vibration under Different Inlet Probe Configurations. (2nd December 2020) - Yang, Rongfei; Wang, Guoliang; Liu, Haixu; Xiang, Honghui; Gao, Jie
Abstract : In the performance test of a compressor, the overstrain alarm of a rotor blade occurred and it was thought to be caused by a large-sized inlet probe. To explain and further avoid the occurrence of this phenomenon, the influences of probe strut configuration on the vibration strain of the compressor rotor blade and the corresponding flow mechanism are studied by using a one-way fluid-structure coupling calculation method. Firstly, the probe strut is simplified as a cylinder with a diameter of 10 mm and located upstream of the inlet stator with the strut wake impinging on the stator blade according to the compressor test. Then, the three scenarios are considered: moving the strut away from the stator blade in axial direction, shifting the strut half of the stator pitch circumferentially, and reducing the strut diameter. The analysis results show that the characteristics of blade vibration are determined by the excitation force on the rotor blade. Under the interaction between the large-sized strut and the compressor, in addition to the excitation force with the strut passing frequency, a force with a lower frequency, namely, the strut-wake-induced frequency, is also observed. The amplitude of the excitation force on the rotor blade depends on the probe configuration. When one of the excitation force frequencies is close to a natural frequency of the rotor blade, the blade resonates, and the amplitude of blade strain varies with the amplitude of the excitation force. In order to reduce the adverse effect of upstream strut wake on the compressor rotor blade vibration, the inlet probe strut should be designed with a smaller diameter and be placed further upstream of the stator in such a way that the strut wake vortex passes through the midpassage of the following stator.